DAMPAK MENEJEMEN KELAS DENGAN PEMISAHAN GENDER (STUDI KASUS DI MA RAUDLATUL MUSTHOFA) - Faudina Permatasari; Vindhy Dian Indah Pratika; Evi Fitriana (STAI Nurul Falah Airmolek, 2024)
Education is the main thing in education, this article reviews the impact of the education model at MA Raudlatul Musthofa, which implements class management with gender separation. This excellent program aims to improve students' spiritual, moral, and academic dimensions. The study observed that by segregating students based on gender and integrating the values of Islamic manners, the school seeks to create a holistic learning environment. This research explores the implementation of this educational model with a focus on the impact on students' behavior, learning spirit, and character. The research method used is descriptive qualitative with a case study approach, involving participatory observation and interviews with relevant stakeholders. The results show that the program is successful in improving discipline, flexibility in learning. Gender separation affects especially students' communication patterns with the opposite sex, but the approach brings a great positive impact to the family and the world of education.